Analysis of Acoustic Attenuation Spectra of Lipon Glasses - Hockicko, Peter; Munoz, Francisco; Bury, Peter; Sidor, Peter (Communications - Scientific letters of the University of Zilina, 2010)
The acoustic attenuation spectra which reflect the basic features of the relaxation and transport processes of the mobile ions of investigated phosphate and oxynitride phosphate glasses are analyzed. Suitable theoretical models and mathematical fit of acoustic spectra are used for characterization of the ionic hopping motion, relaxation processes and transport mechanisms connected with the mobility of conductive ions. Results from acoustic measurements are compared with results obtained from electrical conductivity measurements.